Problematic Aspects of Attributing Assocations to Public Administration Bodies - Vitkutė, Evelina Agota Agota (Teisė, 2018)
The article analyses legal regulation stipulating that associations, authorized by special laws, may perform public administration functions and case law that defines when such associations are or, on the contrary, are not regarded as public administration subjects; the rationale of such legal regulation and case law is assessed. Also, it is also analysed how activities of associations, authorized to perform public administration functions, are compliant with the doctrine of associations’ autonomy from the public government. It is concluded that possibility for the said associations to act in the field of public administration has constitution grounds and it is recommended for the courts to apply unified functional test for assessing the activities of such associations in the field of public administration. Also, it is suggested to clearly distinguish a separate category of associations, establishment, structure and functions thereof, are determined by specific laws.
Keywords: none